Constant-rate perfused array chip for high-throughput screening of drug permeability through brain endothelium. Issue 23 (25th October 2022) - Xiao, Rong-Rong; Jing, Bolin; Yan, Lei; Li, Jiajia; Tu, Pengfei; Ai, Xiaoni
Abstract : A constant-rate perfused array chip (cPAC) that enables constant-rate and high-throughput flow, as well as real-time transendothelial electrical resistance measurement was developed for screening drug permeability through brain endothelium. Abstract : The development of an in vitro model for predicting drug permeability through the human blood–brain barrier (BBB) will greatly accelerate the development of neural therapy. Previously reported platforms for BBB model construction cannot meet the requirements of constant-rate and high-throughput flow, as well as compatibility with the commercial meter for real-time transendothelial electrical resistance (TEER) measurement. Herein, a constant-rate perfused array chip (cPAC) was developed to establish a brain endothelium model for screening drug permeability. The cPAC consisted of 24 units with four layers. Three reservoirs on the top had a 0.5 mm center-to-center spacing, enabling real-time detection of the TEER with the commercial volt–ohm meter. With the optimized chip design, the constant-rate and high-throughput flow by gravity was achieved. Compared with the static culture of the Transwell, the brain endothelium model on the cPAC exhibited superior performance in barrier function, efflux functionality of the transporters, and reversible osmotic opening of the brain endothelium. More importantly, the permeability of model drugs on the cPAC matched the in vivo results with the correlation coefficient reaching 0.994. Finally, the brain endothelium model was cocultured with 3D tumor cells for simultaneous evaluation of drug permeability and brain tumor therapy. The drug efficacy at the target cells on the coculture model was also consistent with clinical findings. These results demonstrated that this platform provides a promising tool for brain endothelium model establishment to predict drug permeability and brain therapy. We anticipate the cPAC to be widely accepted for establishing various barrier models.